How we implemented an analytical support clinic to strengthen student research capacity in Zambia. (July 2015) - Andrews, Ben; Musonda, Patrick; Simuyemba, Moses; Wilson, Craig M.; Nzala, Selestine; Vermund, Sten H.; Michelo, Charles
Abstract Background: Research outputs in sub-Saharan Africa may be limited by a scarcity of clinical research expertise. In Zambia, clinical and biomedical postgraduate students are often delayed in graduation due to challenges in completing their research dissertations. We sought to strengthen institutional research capacity by supporting student and faculty researchers through weekly epidemiology and biostatistics clinics. Methods: We instituted a weekly Analytical Support Clinic at the University of Zambia, School of Medicine. A combination of biostatisticians, clinical researchers and epidemiologists meet weekly with clients to address questions of proposal development, data management and analysis. Clinic sign-in sheets were reviewed. Results: 109 students and faculty members accounted for 197 visits to the Clinic. Nearly all clients (107/109, 98.2%) were undergraduate or postgraduate students. Reasons for attending the Clinic were primarily for proposal development (46.7%) and data management/analysis (42.1%). The most common specific reasons for seeking help were data analysis and interpretation (36.5%), development of study design and research questions (26.9%) and sample size calculation (21.8%). Conclusions: The Analytical Support Clinic is an important vehicle for strengthening postgraduate research through one-on-one and small group demand-driven interactions. The clinic approach supplements mentorship from departmental supervisors, providing specific expertise and contextual teaching.